(untitled) (MAUSAM, 2026)
Over the last 25 years, the World Meteorological Organization through its Working Group on Tropical Meteorology Research carried out a major international collaboration effort to foster monsoon research and forecast centered around the series of International Workshops on Monsoons (IWM). This paper reviews the history of this activity and discusses its development and evolution that contributed significantly to the progress of monsoon research and forecast. Throughout this period the concept, scope and depth of monsoon research have all advanced considerably.